Controlling mid-infrared plasmons in graphene nanostructures through post-fabrication chemical doping. (7th May 2021) - Paulillo, Bruno; Bareza, Nestor Jr; Pruneri, Valerio
Abstract: Engineering the doping level in graphene nanostructures to yield controlled and intense localized surface plasmon resonance (LSPR) is fundamental for their practical use in applications such as molecular sensing for point of care or environmental monitoring. In this work, we experimentally study how chemical doping of graphene nanostructures using ethylene amines affects their mid-infrared plasmonic response following the induced change in electrical transport properties. Combining post-fabrication silanization and amine doping allows to prepare the surface to support a strong LSPR response at zero bias. These findings pave the way to design highly doped graphene LSPR surfaces for infrared sensors operating in real environments.